Private expropriation against the public interest in Iran - Abadi, Mohammad Reza Momen; Sharafatpeima, Mohammadreza (Ciência e Natura, 2015)
Private ownership is the fundamental rights of individuals in the society and having high jurisprudence and legal support. However, in contrast to public interest, administrative agencies can apply to withdraw the property, although there are evidences for the arbitrariness of the legal nature of administrative agencies. It seems that the unilateral obligation of this action is preferred. Expropriation is in contrary to the principles, therefore for health acquisition, the ceremony which is prescribed by lawyer that non-compliance will invalidate the ownership.